INVESTIGATION OF ADS-B MESSAGES TRAFFIC VIA SATELLITE COMMUNICATION CHANNEL - Kharchenko, Volodymyr; Bo, Wang; Grekhov, Andrii; Kovalenko, Marina (Proceedings of National Aviation University (archive), 2014)
For modelling of ADS-B messages transmition with the help of low-orbit satellite complex Іrіdіumdifferent models of communication channel "Aircraft-to-Satellites-to-Ground Stations" were built using NetCrackerProfessіonal 4.1 software. Influence of aircraft and satellites amount on average link utilization and message travellingtime was studied for telecommunication channels with intersatellite link and bent-pipe architecture. The effect ofcommunication channel "saturation" during simultaneous data transmission through a satellite communicationchannel from many planes was investigated.